2019
DOI: 10.1177/0192513x19868257
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Desires of Childless Poles: Which Childbearing Motives Matter for Men and Women?

Abstract: In modern societies, a growing number of people choose to remain childless. As childlessness has fundamental consequences for individuals and societies, it is of paramount importance to understand this choice. We investigate which childbearing motives are related to low-fertility desire of Poles, deterring them from wanting to have children? We look at the motivations of 939 nulliparous men and women, aged 25 to 44 years, who completed the Childbearing Questionnaire as a part of the study on reasons for childl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
2
20
1
2
Order By: Relevance
“…The variables having or not having children and age were presented as predictor variables for both PCM and NCM, corroborating the results of other studies (Irani & Khadivzadeh, 2019;Miller & Pasta, 1995;Mynarska & Rytel, 2020). The variable not having children showed greater predictive power for NCM.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The variables having or not having children and age were presented as predictor variables for both PCM and NCM, corroborating the results of other studies (Irani & Khadivzadeh, 2019;Miller & Pasta, 1995;Mynarska & Rytel, 2020). The variable not having children showed greater predictive power for NCM.…”
Section: Discussionsupporting
confidence: 88%
“…It is important to mention that labor market participation is an unstable variable over the life course, since multiple entries and exits from the labor market may occur for personal reasons or superseded by the economic situation of the country at the time of job search (Smeha & Calvano, 2009). On the other hand, women presented higher levels of NCM than men, corroborating findings of studies conducted in other contexts (Alexander et al, 2019;Mynarska & Rytel, 2020). With women's access to education, insertion in the labor market and the reduced participation of men in domestic activities, educational practices and parenting tasks, women presented greater difficulties in reconciling family and professional life, which makes it understandable that the negative aspects of motherhood are more heavily weighted (Miranda-Ribeiro et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Among women, two positive motives, "feeling needed and connected" and "joys of pregnancy, birth, and infancy" were identified as being predictive of stronger childbearing desire. Among men, the significant predictors of stronger childbearing desire were "satisfaction of child-rearing" and "traditional parenthood" (Mynarska & Rytel, 2020). In societies like India, the sex composition of children is associated with the desire for an additional child.…”
Section: Child Desirementioning
confidence: 99%
“…In turn, these large parental investments, which increase the overall cost of having children, can be posited as influencing decisions around having children. For instance, a recent study in Poland showed that men and women who perceive childrearing as demanding in terms of time, energy, and money express a weaker desire for parenthood (Mynarska and Rytel 2020). Further refinement of the measurement of intensive parenting norms is certainly needed.…”
Section: Discussionmentioning
confidence: 99%